Оцінка впливу освіти на формування ринку праці України - Заюков, І.В. (Інститут демографії та соціальних досліджень НАН України, 2007)
В статье рассматривается проблема дисбаланса на рынке труда, которая связана с несоответствием объемов и структуры профессиональной подготовки кадров профессионально-техническими и высшими учебными учреждениями потребности экономики Украины в рабочей силе. Предложено актуальное направление, позволяющее сбалансировать спрос на рынке труда за счет реализации эффективных инновационных методов профессионального обучения экономически активного населения. The article deals with the problem of disbalance on the labor market. It is connected with non correspondence between professional qualificational structure of professional training and professional technical educational institutions to economic demands of Ukraine. The actual way is offered which allows to balance the demand on the labor market in respect of realization the modern approaches to economically active population professional training.